The Effect of B, Al, N, and P Impurities on the Electronic Structure of Si0.3Sn0.7Ge alloy: A First-Principles Approach - Ouserigha, Collins E.; Benjamin, Ayibapreye K. (European Scientific Journal, ESJ, 2022)
This study examines the effect of doping Si0.3Sn0.7Ge with an impurity element X (B, Al, N, or P) on the Sn site, using first-principle calculations based on the fully self-consistent Korringa-Kohn-Rostoker method with the coherent potential approximation (KKR-CPA). To treat several forms of chemical disorders of Si0.3Sn0.7Ge, X-doping was carried out by substituting small amounts of Sn with each element X, which gives rise to the alloy Si0.3Sn0.7-yXyGe. As the X content increases from y = 0.01 to 0.06, the Fermi level maintains its position in the conduction band edge. While the number of states at the Fermi level decreases. With 1% X impurity added to the alloy Si0.3Sn0.7-yXyGe, the number of carriers (electron and hole) states was generally enhanced. For the case of X = P, when compared to the parent material Si0.3Sn0.7Ge, an enhancement of 0.04 states/eV was observed. Due to the increase in the number of states, which indicates an improvement in thermopower, these alloys Si0.3Sn0.7-yXyGe are promising for application as n-type electrodes in a thermoelectric generator (TEG).